1991
DOI: 10.1002/aja.1001900306
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric study of the prepubertal rabbit testis: Germ cell numbers and seminiferous tubule dimensions

Abstract: Testes from rabbits aged 1-9 weeks were examined by light microscopy. Changes in seminiferous tubule dimensions, testicular volume, and volume fraction of tubules were assessed. Germ cells and Sertoli cells were counted in round tubular cross sections and total germ cell number in each testis was estimated. Mitotic, meiotic, and degenerative activities of germ cells as well as their basal or central positions within tubules were quantified. A marked, steady increase in testis volume and in tubular length and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Considering that RA induces meiosis in both sexes, this probably indicates that in the testis, an RA-dependent stimulus could induce meiosis in the same way as in ovaries around birth. This concurs with previously reported observations of XY germ cells at the preleptoten stage in rabbit testes at around birth and for two weeks after [5], [7], [8]. In the present study as well, the presence of preleptoten like figures at 7 and 18 dpp indicates that meiosis was initiated in the testes but aborted thereafter since no more advanced stages of meiosis were further detected.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Considering that RA induces meiosis in both sexes, this probably indicates that in the testis, an RA-dependent stimulus could induce meiosis in the same way as in ovaries around birth. This concurs with previously reported observations of XY germ cells at the preleptoten stage in rabbit testes at around birth and for two weeks after [5], [7], [8]. In the present study as well, the presence of preleptoten like figures at 7 and 18 dpp indicates that meiosis was initiated in the testes but aborted thereafter since no more advanced stages of meiosis were further detected.…”
Section: Discussionsupporting
confidence: 94%
“…Finally, ovocytes are blocked at the diploten stage [5]. In XY rabbit, several authors have reported figures of germ cells in the preleptoten stage before birth, at the same stage as in the female, without any signs of further true meiosis; however, the first signs of true meiosis were only observed in the male 2–3 months after birth [5], [7], [8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In search for a better parameter than postnatal age we found that the tubular diameter, which increases postnatally from about 50 µm to about 200 µm, reflects more reliably the developmental state of its germ cell population. Thus, the situation in the postnatal prepubertal bovine differs from that in the rabbit for which a marked steady increase in tubular length, but no increase in tubular diameter over the prepubertal period is reported (Iczkowski et al 1991). For the study of germ cell behavior in the prenatal and perinatal bovine testis, the developmental age can be used as a suitable scale of reference.…”
Section: Introductionmentioning
confidence: 96%